Pengaruh Literasi Keuangan Terhadap Pengelolaan Keuangan Pribadi Mahasiswa STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga - Halawa, Valentina Murniwati; Bate’e, Maria Magdalena; Hulu, Perlindungan F.; Bu’ulolo, Nanny A. (Visi Sosial Humaniora, 2024)
This research aims to find out whether financial literacy has an effect positive towards the personal financial management of STP Dian Mandala Students, to find out how much influence financial literacy has in managing students personal finances, and to find out whether financial literacy can overcome students difficulties in having high consumer behavior towards managing students personal finances. The research was conducted at the STP Dian Mandala Gunungsitoli Nias Campus, Sibolga Diocese. The research method used is a quantitative method with data collection through distributing questionnaires, documentation, and interviews, observation. The respondents in this research were 64 students respondents. The results of this research show that the influence of financial literacy has a very significant influence on students personal financial management, amounting to 71.2%. With increased financial literacy, students will increasingly be able to manage their finances wisely, carefully and regularly by applying indicators from each financial literacy variable and personal financial management variable so that students can prepare for their needs and finances in the future.